Founding aspects of contemporary relations between Wallmapu, Chile and Argentina (Estudios Sociales, 2023)
The article focuses on the war that the States of Chile and Argentina carried out against the Mapuche people in the second half of the 19th century. Through period sources and the works of authors/s that also incorporate the Mapuche voices and letters, the phenomena of war, the livestock economy and violence are reviewed and discussed, which allows us to conclude that there was a break in the logic of the political pact for that of subordination, appropriating not only resources such as land or cattle, but also fracturing social bodies through genocide. These facts found a contemporary time that incubated the colonial situation and relationship that continues to this day.
Keywords: racism